Net‐Zero CO2 Germany—A Retrospect From the Year 2050. Issue 2 (11th February 2022) - Mengis, Nadine; Kalhori, Aram; Simon, Sonja; Harpprecht, Carina; Baetcke, Lars; Prats‐Salvado, Enric; Schmidt‐Hattenberger, Cornelia; Stevenson, Angela; Dold, Christian; El Zohbi, Juliane; Borchers, Malgorzata; Thrän, Daniela; et al.
Abstract: Germany 2050: For the first time Germany reached a balance between its sources of anthropogenic CO2 to the atmosphere and newly created anthropogenic sinks. This backcasting study presents a fictional future in which this goal was achieved by avoiding (∼645 Mt CO2 ), reducing (∼50 Mt CO2 ) and removing (∼60 Mt CO2 ) carbon emissions. This meant substantial transformation of the energy system, increasing energy efficiency, sector coupling, and electrification, energy storage solutions including synthetic energy carriers, sector‐specific solutions for industry, transport, and agriculture, as well as natural‐sink enhancement and technological carbon dioxide options. All of the above was necessary to achieve a net‐zero CO2 system for Germany by 2050. Plain Language Summary: Here a net‐zero‐2050 Germany is envisioned by combining analysis from an energy‐system model with insights into approaches that allow for a higher carbon circularity in the German system, and first results from assessments of national carbon dioxide removal potentials. A back‐casting perspective is applied on how net‐zero Germany could look like in 2050. We are looking back from 2050, and analyzing how Germany for the first time reached a balance between its sources of CO2 to the atmosphere and the anthropogenic sinks created. This would consider full decarbonization in the entire energy sector and being entirely emission‐free by 2050 within three priorities identified as being the most useful strategies for achieving net‐zero: (a) Avoiding‐ (b) Reducing‐ (c) Removing emissions. This work is a collaboration of interdisciplinary scientists with the Net‐Zero‐2050 cluster of the Helmholtz Climate Initiative HI‐CAM. Key Points: The net‐zero system shows that for countries like Germany, avoiding CO2 emissions was the largest contribution to achieve net‐zero CO2 With the three strategies of emissions avoidance, reduction, and removal, Germany has achieved its net‐zero CO2 goal for the first time In addition, to natural sink enhancement carbon dioxide removal (CDR) options, technological CDR measures combined with geological CO2 storage were necessary to reach net‐zero CO2